2004
DOI: 10.1098/rspa.2004.1293
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a liquid lamella resulting from the impact of a water drop on a small target

Abstract: International audienceThe dynamics of a circular liquid lamella resulting from the collision of a water drop with a small disc-like target was studied experimentally and theoretically. Such a type of collision also acts as a model of drop impacts on plane surfaces in the absence of liquid friction, and therefore for more widespread collisions of drops of inviscid liquid with solid surfaces. We propose a simple model to describe the dynamics of the lamella resulting from the drop impact and also predict the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
85
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(103 citation statements)
references
References 13 publications
18
85
0
Order By: Relevance
“…The symmetry breaking apparent on the distorted rim (on can tell the direction of the acceleration by looking at still pictures) where thicker portions of the rim are "left behind" thinner ones while accelerated at constant force, 12 together with the fair quantitative agreement between the observations and Eq. (4) both tend to support the relevance of the Rayleigh-Taylor scenario: The driving force is inertia (acceleration), and the mode selection is made by capillarity.…”
supporting
confidence: 50%
“…The symmetry breaking apparent on the distorted rim (on can tell the direction of the acceleration by looking at still pictures) where thicker portions of the rim are "left behind" thinner ones while accelerated at constant force, 12 together with the fair quantitative agreement between the observations and Eq. (4) both tend to support the relevance of the Rayleigh-Taylor scenario: The driving force is inertia (acceleration), and the mode selection is made by capillarity.…”
supporting
confidence: 50%
“…A similar scenario has been observed when a viscous drop impacts a thin layer of liquid with a lower surface tension [22]. For pure water (no oil droplets), no perforation occurs and the sheet uniquely disintegrates through the destabilization of the external rim into drops [12]. Thanks to the dye, the modulations of the sheet thick- ness are visualized.…”
mentioning
confidence: 77%
“…But, to the best of our knowledge, those conditions have never been confronted to robust experimental facts. To unambiguously clarify the physical mechanisms at play, rationale experiments on individual perforation events are therefore required.In this Letter, we investigate the perforation mechanisms of an emulsion-based free liquid sheet issued from a single-drop experiment; resulting from the impact of one drop of fluid onto a small target [12][13][14]. During the sheet expansion, holes nucleate and grow.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent researches reported that, in 3D environments, E-cadherin deficiency indeed led to a loss of intercellular adhesion and triggered tumor cell invasion by matrix MMP-2 and MMP-9 driven matrix degradation. Surface tension at the tumor-tissue interface, have been extensively studied in the field of fluid dynamics (44,45,46,47). Promoting tumor cell adhesion and thus increasing the tumor surface tension can induce cellular cohesiveness and decreasing of the invasiveness.…”
Section: Physical Factors and Reciprocitymentioning
confidence: 99%